Nivel de conocimiento de farmacovigilancia del personal de salud de la Micro Red Jose Antonio Encinas, Puno 2024. - Hilasaca Araujo, Paola Stephanie; Perez Quispe, Gledy (Universidad Privada de Huancayo Franklin RooseveltP, 2024)
La investigación tuvo como objetivo determinar el nivel de conocimiento en farmacovigilancia del personal de salud de la Micro Red José Antonio Encinas ubicada en Puno, enero a febrero del 2024. La investigación fue de tipo descriptiva y básica, la muestra del estudio fue constituida por 75 profesionales de la salud. Se reportó que los técnicos en enfermería realizan el mayor número de notificaciones RAM (41.3%), el 76.5% acertaron las preguntas de conceptos básicos de farmacovigilancia, el 23.33% las preguntas en métodos empleados en farmacovigilancia y el 41.33% las preguntas del proceso de farmacovigilancia. Se concluye que el personal de salud de la Micro Red José Antonio Encinas ubicada en Puno, presentaron un nivel de conocimiento alto en farmacovigilancia.

The objective of the research was to determine the level of pharmacovigilance knowledge of the health personnel of the José Antonio Encinas Micro-Network located in Puno, January to February 2024. The research was descriptive and basic, the study sample consisted of 75 health professionals. It was reported that nursing technicians made the highest number of RAM notifications (41.3%), 76.5% were correct in the questions on basic pharmacovigilance concepts, 23.33% in the questions on methods used in pharmacovigilance and 41.33% in the questions on the pharmacovigilance process. It is concluded that the health personnel of the José Antonio Encinas Micro-Network located in Puno had a high level of knowledge in pharmacovigilance.
Level of knowledge of pharmacovigilance of health personnel in the Micro Red health personnel of the Jose Antonio Encinas Micro-Network, Puno 2024.
Keywords: Farmacovigilancia; Nivel de conocimiento; Micro Red José Antonio Encinas; http://purl.org/pe-repo/ocde/ford#3.01.05